Designing a MIT App Inventor-based mathematics learning application to enhance students’ conceptual understanding: A development study - Wijaya, Aryo Surya (Pi Radian: Journal of Mathematics Education, 2025)
The background of this study lies in the limited use of technology-based learning media, which is essential to improve the quality of learning. Therefore, this research aims to: (1) describe the process of developing a mathematics learning application using MIT App Inventor, (2) examine the validity of the developed application, (3) measure its effectiveness, (4) assess its practicality, and (5) analyze students’ responses to the application. The research employed a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 29 students of class VIII-A at SMP Negeri 24 Bandung during the 2022/2023 academic year. Research instruments included validation questionnaires for material experts and media experts, a practicality questionnaire, post-test sheets, and a student response questionnaire. The results of the analysis indicate that the developed mathematics learning application is categorized as good, with a validation score of 86.33 (very valid) from material experts and 70.5 (valid) from media experts. The level of effectiveness was 82.76 (very effective), practicality was 82.29 (practical), and students’ response score was 75.78 (fairly good). These findings suggest that the application developed with MIT App Inventor can serve as a valid, effective, and practical medium for supporting students’ conceptual understanding in mathematics learning. This study contributes by providing an empirically validated development framework and practical reference for integrating MIT App Inventor-based applications into junior high school mathematics instruction to enhance conceptual understanding.